Food Reputation and Food Preferences: Application of the Food Reputation Map (FRM) in Italy, USA, and China - De Dominicis, Stefano; Bonaiuto, Flavia; Fornara, Ferdinando; Ganucci Cancellieri, Uberta; Petruccelli, Irene; Crano, William D.; Ma, Jianhong; Bonaiuto, Marino (Frontiers in Psychology, 2020)
Given the food challenges that society is facing, we draw upon recent developments in the study of how food reputation affects food preferences and food choices, providing here a starting standard point for measuring every aspect of food reputation in different cultural contexts across the world. Specifically, while previous attempts focused either on specific aspects of food or on measures of food features validated in one language only, the present research validates the Food Reputation Map (FRM) in Italian, English and Chinese over 2250 participants worldwide. Here we successfully measure food reputation across twenty-three specific indicators, further grouped into six synthetic indicators of food reputation. Critically, results show that: a) the specific measurement tool of food reputation can vary across cultural contexts, and that b) people’s reputation of food products or categories changes significantly across different cultural contexts. Therefore, in order to understand people’s food preferences and consumption, it is important to take into account the repertoire of cultural differences that underlies the contexts of analysis: the three context-specific versions of the FRM presented here effectively deal with this issue and provide reliable context-specific insights on stakeholders’ interests, perspectives, attitudes and behaviors related to food perceptions, assessment and consumption, which can be effectively leveraged to foster food sustainability.